2019
DOI: 10.1371/journal.pgen.1007976
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial proline catabolism activates Ras1/cAMP/PKA-induced filamentation in Candida albicans

Abstract: Amino acids are among the earliest identified inducers of yeast-to-hyphal transitions in Candida albicans , an opportunistic fungal pathogen of humans. Here, we show that the morphogenic amino acids arginine, ornithine and proline are internalized and metabolized in mitochondria via a PUT1 - and PUT2 -dependent pathway that results in enhanced ATP production. Elevated ATP levels correlate with Ras1/cAMP/PKA pathway activation and Efg1-induced… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

27
152
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(182 citation statements)
references
References 107 publications
27
152
3
Order By: Relevance
“…Although CaSsy1 and ScSsy1 share a high degree of homology in the C-terminal domains, their N-terminal-sensing domains are highly divergent [52]. It is likely that this explains the altered CaSsy1 substrate specificity: the highest induction occurs in the presence of Arg, Asn, Asp, Gln, Glu, His, Lys, and Ser, while the other amino acids fail to stimulate the sensor [22,52]. Further differences can be found in the downstream effectors CaStp1 and CaStp2 which, contrary to S. cerevisiae, exhibit a clear dichotomy in their regulatory activity: while the CaStp1 regulon contains genes required for protein utilization; like secreted aspartyl proteases (SAP) and oligopeptide transporters (OPT), CaStp2 is required for the expression of AAPs [53].…”
Section: Scgap1mentioning
confidence: 99%
“…Although CaSsy1 and ScSsy1 share a high degree of homology in the C-terminal domains, their N-terminal-sensing domains are highly divergent [52]. It is likely that this explains the altered CaSsy1 substrate specificity: the highest induction occurs in the presence of Arg, Asn, Asp, Gln, Glu, His, Lys, and Ser, while the other amino acids fail to stimulate the sensor [22,52]. Further differences can be found in the downstream effectors CaStp1 and CaStp2 which, contrary to S. cerevisiae, exhibit a clear dichotomy in their regulatory activity: while the CaStp1 regulon contains genes required for protein utilization; like secreted aspartyl proteases (SAP) and oligopeptide transporters (OPT), CaStp2 is required for the expression of AAPs [53].…”
Section: Scgap1mentioning
confidence: 99%
“…On the one hand, mitochondrial respiration can affect the morphogenesis of fungi. For instance, high ATP levels resulting from mitochondrial respiratory activity have been shown to be crucial for C. albicans to switch from yeast cells to mycelium growth [ 20 , 64 , 65 ]. Because this morphogenetic transition is thought to be related to C. albicans virulence [ 66 ], this result shows that mitochondrial respiration can mediate C. albicans virulence by affecting morphogenetic transition.…”
Section: Roles Of Mitochondria In Fungal Pathogenicitymentioning
confidence: 99%
“…For example, Grahl et al (2015) reported that in C. albicans, the disease-associated morphological switch from yeast to hyphal growth is affected by mitochondrial functions, as mitochondrial inhibitors potently suppress the Ras1-Cyr1-PKA pathway, a major regulator of C. albicans morphogenesis, biofilm formation, and white-opaque switching. Furthermore, Silao et al (2019) reported that induced respiration is critical for morphogenesis during the catabolism of morphogenic amino acids, which is an important feature for C. albicans to evade macrophages. C. albicans cells are highly adaptive to the inhibition of classical respiration; however, a recent study reported that a combination of AOX inhibitor salicylhydroxamic acid (SHAM) and sodium nitroprusside lead to fitness defects and the loss of viability in C. albicans (Duvenage et al, 2019).…”
Section: Aox and Fungal Virulencementioning
confidence: 99%